bpMRI and mpMRI for detecting prostate cancer: A retrospective cohort study - Pan, Yongsheng; Shen, Cheng; Chen, Xinfeng; Cao, Dongliang; Jiang, Jie; Xu, Wei; Ji, Chen; Pan, Xiaodong; Zheng, Bing (Frontiers in Surgery, 2023)
Background: We aimed to compare the detection rates of prostate cancer (PCa) and clinically significant prostate cancer(csPCa) by biparametric (bp-) and multiparameter magnetic resonance imaging (mpMRI). Materials and Methods: A total of 699 patients who underwent transperineal prostate biopsy in the Department of Urology, the Second Affiliated Hospital of Nantong University from January 2018 to December 2021 were retrospectively reviewed. Multivariate analysis was used to explore the influencing factors associated with the detection rates of PCa and csPCa. According to MRI examination before biopsy, the patients were divided into bpMRI group and mpMRI group. The detection rates of PCa and csPCa by bpMRI and mpMRI were compared. Furthermore, stratified analysis was performed for patients in these two groups to compare the detection rates of PCa and csPCa at different tPSA intervals, different prostate volume(PV) intervals and different PI-RADS V2 scores. Results: A total of 571 patients were finally analyzed in this study after exclusion, and the overall detection rate of PCa was 54.5%. Multivariate analysis showed that patient age, tPSA level, prostate volume and PI-RADS V2 score were independent risk factors affecting the detection rates of PCa and csPCa. The detection rates of PCa and csPCa by bpMRI and mpMRI were comparable (51.3% vs. 57.9%, 44.0% vs. 48.0%, both P > 0.05), with no statistical significance. In the tPSA 10 – 20 ng/mL interval, the detection rates of PCa (59.72% vs 40.35%, P = 0.011) and csPCa (51.39% vs 28.82%, P = 0.005) by mpMRI were significantly higher than those by bpMRI, while in other tPSA interval (tPSA < 4 ng/mL, 4 – 10 ng/mL, 20 – 100 ng/mL), different PVs (≤ 30 mL, 30 – 60 mL, > 60 mL) and different PI-RADS V2 scores (3, 4, and 5), the detection rates of PCa and csPCa were comparable between the two groups. Conclusion: For detecting PCa and csPCa, bpMRI and mpMRI had similar diagnostic efficacies, whereas mpMRI detected more PCa and csPCa in the tPSA interval of 10-20 ng/ml.